Solution/Ammonolysis Syntheses of Unsupported and Silica-Supported Copper(I) Nitride Nanostructures from Oxidic Precursors - Robert Szczęsny; Tuan K. A. Hoang; Liliana Dobrzańska; Duncan H. Gregory (Molecules, 2021)
Herein we describe an alternative strategy to achieve the preparation of nanoscale Cu3N. Copper(II) oxide/hydroxide nanopowder precursors were successfully fabricated by solution methods. Ammonolysis of the oxidic precursors can be achieved essentially pseudomorphically to produce either unsupported or supported nanoparticles of the nitride. Hence, Cu3N particles with diverse morphologies were synthesized from oxygen-containing precursors in two-step processes combining solvothermal and solid−gas ammonolysis stages. The single-phase hydroxochloride precursor, Cu2(OH)3Cl was prepared by solution-state synthesis from CuCl2·2H2O and urea, crystallising with the atacamite structure. Alternative precursors, CuO and Cu(OH)2, were obtained after subsequent treatment of Cu2(OH)3Cl with NaOH solution. Cu3N, in the form of micro- and nanorods, was the sole product formed from ammonolysis using either CuO or Cu(OH)2. Conversely, the ammonolysis of dicopper trihydroxide chloride resulted in two-phase mixtures of Cu3N and the monoamine, Cu(NH3)Cl under similar experimental conditions. Importantly, this pathway is applicable to afford composite materials by incorporating substrates or matrices that are resistant to ammoniation at relatively low temperatures (ca. 300 °C). We present preliminary evidence that Cu3N/SiO2 nanocomposites (up to ca. 5 wt.% Cu3N supported on SiO2) could be prepared from CuCl2·2H2O and urea starting materials following similar reaction steps. Evidence suggests that in this case Cu3N nanoparticles are confined within the porous SiO2 matrix.